Treatment with two different doses of sonidegib in patients with locally advanced or metastatic basal cell carcinoma (BOLT): a multicentre, randomised, double-blind phase 2 trial. Issue 6 (June 2015) - Migden, Michael R; Guminski, Alexander; Gutzmer, Ralf; Dirix, Luc; Lewis, Karl D; Combemale, Patrick; Herd, Robert M; Kudchadkar, Ragini; Trefzer, Uwe; Gogov, Sven; Pallaud, Celine; Yi, Tingting; et al.
Summary: Background: Patients with advanced basal cell carcinoma have limited treatment options. Hedgehog pathway signalling is aberrantly activated in around 95% of tumours. We assessed the antitumour activity of sonidegib, a Hedgehog signalling inhibitor, in patients with advanced basal cell carcinoma. Methods: BOLT is an ongoing multicentre, randomised, double-blind, phase 2 trial. Eligible patients had locally advanced basal cell carcinoma not amenable to curative surgery or radiation or metastatic basal cell carcinoma. Patients were randomised via an automated system in a 1:2 ratio to receive 200 mg or 800 mg oral sonidegib daily, stratified by disease, histological subtype, and geographical region. The primary endpoint was the proportion of patients who achieved an objective response, assessed in the primary efficacy analysis population (patients with fully assessable locally advanced disease and all those with metastatic disease) with data collected up to 6 months after randomisation of the last patient. This trial is registered withClinicalTrials.gov, numberNCT01327053 . Findings: Between July 20, 2011, and Jan 10, 2013, we enrolled 230 patients, 79 in the 200 mg sonidegib group, and 151 in the 800 mg sonidegib group. Median follow-up was 13·9 months (IQR 10·1–17·3). In the primary efficacy analysis population, 20 (36%, 95% CI 24–50) of 55 patients receiving 200 mg sonidegib and 39 (34%, 25–43) of 116 receiving 800 mg sonidegib achieved an objective response. In the 200 mg sonidegib group, 18 (43%, 95% CI 28–59) patients who achieved an objective response, as assessed by central review, were noted among the 42 with locally advanced basal cell carcinoma and two (15%, 2–45) among the 13 with metastatic disease. In the 800 mg group, 35 (38%, 95% CI 28–48) of 93 patients with locally advanced disease had an objective response, as assessed by central review, as did four (17%, 5–39) of 23 with metastatic disease. Fewer adverse events leading to dose interruptions or reductions (25 [32%] of 79 patients vs 90 [60%] of 150) or treatment discontinuation (17 [22%] vs 54 [36%]) occurred in patients in the 200 mg group than in the 800 mg group. The most common grade 3–4 adverse events were raised creatine kinase (five [6%] in the 200 mg group vs 19 [13%] in the 800 mg group) and lipase concentration (four [5%] vs eight [5%]). Serious adverse events occurred in 11 (14%) of 79 patients in the 200 mg group and 45 (30%) of 150 patients in the 800 mg group. Interpretation: The benefit-to-risk profile of 200 mg sonidegib might offer a new treatment option for patients with advanced basal cell carcinoma, a population that is difficult to treat. Funding: Novartis Pharmaceuticals Corporation.